Karakteristik Organoleptik Jelly Drink Buah Gandaria (Macrophylla sp) Dengan Penambahan Carboxymethyl Cellulose - Palijama, Syane (Universitas Pattimura, 2023)
This research aims to characterize the Gandaria jelly drink with the addition of CMC sensory in hedonic tests and hedonic quality which were carried out descriptively. The results of the research showed that jelly drinks with the addition of CMC using hedonic tests had a color ranging between 3.1–3.8 (liked to very liked), taste 3.6–4.0 (liked very much), aroma 3.5–4.0 (like it very much), texture 2.6–3.0 (like it), suction power 2.6–3.0 (like it), and over all 3.8–4.0 (like it very much), while the test Hedonic quality has color ranging between scale values of 2.9–3.3 (yellow), taste 4.0–4.5 (tastes of Gandaria), aroma 4.0–4.5 (smells of Gandaria), texture 2.9–3.6 (springy to very springy) and suction power 2.9–3.6 (easy to suck to very easy to suck).